Term formation and issues of Latin script. (Eurasian Journal of Philology Science and Education, 2015)
The global theme of the Kazakh terminology – the role of the Latin elements in the world of terminology and term formation in the Kazakh language, unification of terms in an official language – has beenconsidered in the article. Errors in creating special terminology in the Kazakh language are taken into account, references to the ideas of scientists and opinions of Kazakh-speaking audience are given. Thereasons for the appearance of inappropriate terms and the ways of creating terms qualitative from the point of view of scientific theories are considered. The authors of the article explain why the terms ofnatural sciences do not have their translation and with reference to the phrase «international terms». The Kazakh vocabulary has been analyzed and considered, it also has a chance for term formation. The samemethods are used in term-formation and in word-formation, because the main problem of terminology is term-formation. From the theoretical point of view the methods of branch term-formation are analyzed. The examples and references from the studies of our scientists and Russian scientists are given.
Keywords: term formation; term field; term vocabulary; terminologist; borrowed terms; transterminology; terminological integration